Magnetostriction Assessment with Strain Gauges and Fiber Bragg Gratings - C. Linhares, Cassiano; Espírito Santo, João; R. Teixeira, Ricardo; P. Coutinho, Cristiano; M.O. Tavares, Sérgio; Pinto, Marta; Costa, João S.; Mendes, Helder; S. Monteiro, Catarina; V. Rodrigues, António; Frazão, Orlando (EAI Endorsed Transactions on Energy Web, 2019)
Power transformers have an imperative role in the future developments of the electrical grids. Treated as crucial assets for transportation and distribution of electrical energy, transformers are currently being studied regarding to the integration of technologies aiming to diagnose problems and monitoring data of electrical power grid. Furthermore, environmental noise pollution has gained importance, especially in active units of the power grid, located near consumers, such as transformers. Transformers noise can be classified according to its source: core, windings and cooling. This study addresses an experimental characterization of one of the main causes of transformers core noise - magnetostriction of electrical steel. An evaluation of magnetostriction properties of electrical steel, including resistive strain gauges and Fiber Bragg Gratings (FBGs) measurements with an Epstein frame, are presented and discussed. The magnetic flux density influence on hysteretic strain behavior of magnetostriction was evaluated, as well as the effect of a clamping load on core joints. Nowadays, optical interrogators for Bragg gratings have a high acquisition frequencies and wavelength sensitivity when compared to former optical interrogation systems, allowing to evaluate physical phenomena without electromagnetic interference and with equivalent resolution of conventional strain gauges.
Keywords: Epstein Frame; FBGs; Magnetostriction; Noise; Power Transformers; Strain Gauges